2008
DOI: 10.1186/cc7150
|View full text |Cite
|
Sign up to set email alerts
|

Association between administered oxygen, arterial partial oxygen pressure and mortality in mechanically ventilated intensive care unit patients

Abstract: Introduction The aim of this study was to investigate whether inhospital mortality was associated with the administered fraction of oxygen in inspired air (FiO 2 ) and achieved arterial partial pressure of oxygen (PaO 2 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
257
4
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(301 citation statements)
references
References 38 publications
18
257
4
12
Order By: Relevance
“…To maintain adequate P aO 2 , F IO 2 is usually set higher than O 2 in ambient air. 1 Although several studies have provided epidemiological data for O 2 administration in critically ill subjects, [1][2][3][4][5] the evidence is insufficient for deciding the best target values for P aO 2 and optimal titration of F IO 2 during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain adequate P aO 2 , F IO 2 is usually set higher than O 2 in ambient air. 1 Although several studies have provided epidemiological data for O 2 administration in critically ill subjects, [1][2][3][4][5] the evidence is insufficient for deciding the best target values for P aO 2 and optimal titration of F IO 2 during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Adverse outcomes of hyperoxemia were identified in patients after cardiac arrest 6 and acute myocardial infarction 7 and in extremely premature infants. 8 Animal studies have demonstrated that high F IO 2 increases free radicals and causes an influx of inflammatory cells in the lung, 9 pulmonary permeability, and endothelial cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] For this reason, it will be necessary to adjust the track and trigger scoring systems to ensure that staff are alerted to the risks of hyperoxaemia as well as of hypoxaemia. Systems are being trialled in which patients are allocated three EWS points if the SpO 2 is above or below the predefined target It will be important to identify the most effective method of managing the clinical response to elevated EWS, but the precise clinical usefulness of METs and RRTs have yet to be proven.…”
Section: Future Directionmentioning
confidence: 99%
“…Oxygen therapy may be a life-saving intervention and is an intervention applied essentially to all intensive care unit (ICU) patients (1). Intensive care clinicians play a vital role in the administration and management of oxygen therapy for patients admitted to the intensive care unit (ICU) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive care clinicians play a vital role in the administration and management of oxygen therapy for patients admitted to the intensive care unit (ICU) (1,2). Evidence from animal (3,4) and human studies (5, 6) has continued to identify the injurious effects of prolonged hyperoxaemia.…”
Section: Introductionmentioning
confidence: 99%